THE REPRESENTATION OF PUJASMARA IN ABUANG DANCE IN TENGANAN PEGRINGSINGAN VILLAGE, MANGGIS DISTRICT, KARANGASEM REGENCY - Ni Ketut Riska Dewi Prawita; I Nyoman Suarka; I Nyoman Linggih (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2023)
Abuang dance is one of the dances that accompany religious ceremony at Usaba Kasa and Usaba Sambah in Tenganan Pegringsingan. The art of dance provides an image of worshiping the greatness of God through beauty, therefore Sang Hyang Smara is believed to be God of worship as God of Beauty. This research is a qualitative research with an ethnographic research approach. The results of the research show that Abuang Dance contains many symbols of Pujasmara that can be internalized to the Tenganan Pegringsingan community, Pujasmara's representation in Abuang Dance is shown by dancers, fashion, property, movement, and selonding gamelan. The belief of the Tenganan Pegringsingan community is a belief in local wisdom based on the desa, kala, patra which cannot be changed, but remains in the teachings of the Hindu religious scriptures that God is One ‘Esa’.